Correlations between Risk Factors for Breast Cancer and Genetic Instability in Cancer Patients—A Clinical Perspective Study - Paz, Márcia Fernanda Correia Jardim; de Alencar, Marcus Vinícius Oliveira Barros; Gomes Junior, Antonio Luiz; da Conceição Machado, Keylla; Islam, Muhammad Torequl; Ali, Eunus S.; Shill, Manik Chandra; Ahmed, Md. Iqbal; Uddin, Shaikh Jamal; da Mata, Ana Maria Oliveira Ferreira; de Carvalho, Ricardo Melo; da Conceição Machado, Kátia; et al. (Frontiers in Genetics, 2018)
Molecular epidemiological studies have identified several risk factors linking to the genes and external factors in the pathogenesis of breast cancer. In this sense, genetic instability caused by DNA damage and DNA repair inefficiencies are important molecular events for the diagnosis and prognosis of therapies. Therefore, the objective of this study was to analyze correlation between sociocultural, occupational and lifestyle risk factors with levels of genetic instability in non-neoplastic cells of breast cancer patients. Total 150 individuals were included in the study that included 50 breast cancer patients submitted to chemotherapy, 50 breast cancer patients submitted to radiotherapy, and 50 healthy women without any cancer. Cytogenetic biomarkers for apoptosis and DNA damage were evaluated in samples of buccal epithelial and peripheral blood cells through micronuclei and comet assay tests. Elder age patients (61 to 80 years) had higher levels of apoptosis (karyorrhexis and catriolysis) and DNA damage at the diagnosis (baseline damage) with increased cell damage during chemotherapy and especially during radiotherapy. We also reported the increased frequencies of cytogenetic biomarkers in patients who were exposed to ionizing radiation as well as for alcoholism and smoking. Chemotherapy and radiotherapy induced high levels of fragmentation (karyorrhexis) and nuclear dissolution (karyolysis) and DNA damage. Correlations were observed between age and karyorrhexis at diagnosis; smoking and karyolysis during radiotherapy; and radiation and karyolysis during chemotherapy. These correlations indicate that risk factors may also influence the genetic instability in non-neoplastic cells caused to the patients during cancer therapies.